(untitled) (Global Journal of Human-Social Science, 2021)
Mobile penetration is remarkably high in Bangladesh due to low tariffs for mobile services inaccessibility on the landline in remote areas and better network coverage by mobile operators Owing to easy accessibility to the internet social media like Facebook is prevalent among the vast majority Women constitute approximately half of the population Operating business on the Facebook platform known as F-commerce Facebook commerce is the recent business trend With the opportunity of browsing through thousands of products from the comfort of their places in flexible times consumers are becoming tempted to shop via Facebook This particular consumer behaviour is triggering thousands of women to become independent entrepreneurs using F-commerce The positive consequence is the unforeseen thrive in F-commerce during the COVID-19 pandemic period when consumers are in fear of contracting the coronavirus in public and retailing stores are staying closed due to lockdown